Das Pflegegeld und die Menschengrundrechte - Kundera, Weronika (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The nursing care benefit (Pflegegeld) in the Republic of Austria is a social benefit granted in order to provide assistance and care to individuals in connection with their inability to live autonomously. In accordance with article 4 of the Bundespflegegeld statute it includes assistance with routine daily activities that are not of a medical nature, such as dressing, undressing, everyday hygienic care, washing, and hair combing, etc. A case concerning the amount of the benefit paid to an elderly woman with long hair has gained a lot of attention. Due to the fact that the care of her hair took more time than prescribed, the social welfare center ordered the applicant to cut her hair. The woman appealed the decision, arguing that the purpose of the nursing care benefit is to improve the situation of the person suffering from senility, which should allow him or her to live in accordance with their needs, expressed e.g. by the right to make decisions concerning one’s appearance. The applicant questioned the decision from the point of view of the benefit’s purpose, arguing that the shortening of the long hair she had for years would worsen her mental state. The Court rejected her arguments, pointing to the fact that the care of an ill member of the society has to fall within reasonable boundaries. A caregiver who provides assistance is only obligated to perform essential activities that are necessary and sufficient to alleviate everyday pain and overcome the difficulties of a senile person, such as helping them with getting up, preparing meals, and apartment cleaning. He or she is not a hair stylist or a beautician, and the activities performed as part of these professions remain outside the caregiver’s professional duties
Keywords: Pflegegeld; Menschenrechte; Recht auf Achtung der Privatsphäre und der Entscheidungsfreiheit; Entscheidungsfreiheit; Pflichten der Pflegegeldbetreuer; Sozialhilfe und gesellschaftliche Interesse